2016
DOI: 10.3944/aott.2016.15.0213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of positive end-expiratory pressure on arthroscopic shoulder surgery under general anesthesia

Abstract: Adding PEEP to the ventilation parameters of arthroscopic shoulder surgery in the beach-chair position reduces the amount of hemorrhage in the surgical field and thus increases surgical satisfaction without requiring the creation of controlled hypotension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Moreover, the patients will have no spontaneous breathing and must be assisted by the mechanical ventilation of the anesthesia machine, which poses a risk for patients with acute and chronic respiratory diseases and cardiovascular diseases and is prone to causing intraoperative hypotension and postoperative breathing inhibition or hypoxemia (Miskovic and Lumb, 2017;Wang et al, 2019). Furthermore, a number of studies have demonstrated that a general anesthesia involving the beach-chair position is prone to causing local cerebral ischemia and hypoxia, which may lead to temporary or permanent neurological complications (Janssen et al, 2014;Ersoy et al, 2016;Ding et al, 2017). All these conclusions were confirmed in the present study.…”
Section: Time Pointmentioning
confidence: 99%
“…Moreover, the patients will have no spontaneous breathing and must be assisted by the mechanical ventilation of the anesthesia machine, which poses a risk for patients with acute and chronic respiratory diseases and cardiovascular diseases and is prone to causing intraoperative hypotension and postoperative breathing inhibition or hypoxemia (Miskovic and Lumb, 2017;Wang et al, 2019). Furthermore, a number of studies have demonstrated that a general anesthesia involving the beach-chair position is prone to causing local cerebral ischemia and hypoxia, which may lead to temporary or permanent neurological complications (Janssen et al, 2014;Ersoy et al, 2016;Ding et al, 2017). All these conclusions were confirmed in the present study.…”
Section: Time Pointmentioning
confidence: 99%